2021
DOI: 10.1002/suco.202000062
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mix composition on the properties of recycled aggregate concrete

Abstract: There is an increasing trend towards using recycled aggregate (RA) in concrete due to the shortage of high quality natural aggregates. The use of RA in concrete results in the conservation of natural resources, protects the environment and encourages sustainable construction. Though some studies have been conducted on the use of recycled aggregate concrete (RAC), the effect of mixture composition on its properties has not been well addressed. In the reported study, the effect of mixture composition, namely cem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Reductions in both the compressive and tensile strengths occurred when the RCA amount increased because of the presence of attached cement mortar in RCA which has a lower strength than that of NCA. The results revealed that RCA can be efficiently used with a percentage of up to 30% as it has an insignificant effect on the compressive strength of concrete, as previously concluded in several studies (Bidabadi et al , 2020) and (Zaben et al , 2021). However, the concrete with RCA of 70% suffered from a significant reduction in the compressive strength, which might not be inappropriate for some applications.…”
Section: Resultssupporting
confidence: 75%
“…Reductions in both the compressive and tensile strengths occurred when the RCA amount increased because of the presence of attached cement mortar in RCA which has a lower strength than that of NCA. The results revealed that RCA can be efficiently used with a percentage of up to 30% as it has an insignificant effect on the compressive strength of concrete, as previously concluded in several studies (Bidabadi et al , 2020) and (Zaben et al , 2021). However, the concrete with RCA of 70% suffered from a significant reduction in the compressive strength, which might not be inappropriate for some applications.…”
Section: Resultssupporting
confidence: 75%
“…In addition to the destruction of natural resources, it imposes a lot of solid waste in the environment. 19,29,32,33,38,39,42,56,62 Abbreviations: AC, curing age; ADR, additive regression; B, total binder; BAG, bagging predictors; CA, coarse aggregate; CS, compressive strength; DT, decision table; GF, glass fiber; GPR, Gaussian process regression; LWL, locally weighted linear; M5R, M5-Rules; MLP, multilayer perceptron; RA, recycled aggregates; RAC, recycled aggregate concrete; REPT, reduced-error pruning tree; RF, random forest; SF, silica-fume; SSD, saturated surface dried; SVR, support vector regression; W, water.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the solid waste of countries is usually caused by construction and demolition in the construction industry. In addition to the destruction of natural resources, it imposes a lot of solid waste in the environment 19,29,32,33,38,39,42,56,62 …”
Section: Introductionmentioning
confidence: 99%
“…RAC has great application potential. 2 However, Noaman et al 3 found that compared with natural aggregate (NA), RA has smaller density and higher water absorption. Cachim 4 also pointed out that RA could be used as partial replacement of NAs in concrete without reduction of concrete properties for 15% replacement and with reductions up to 20% for 30% replacement.…”
Section: Introductionmentioning
confidence: 99%
“…RBA and RCA are called recycled aggregate (RA), RBAC and RCAC are called recycled aggregate concrete (RAC). RAC has great application potential 2 . However, Noaman et al 3 found that compared with natural aggregate (NA), RA has smaller density and higher water absorption.…”
Section: Introductionmentioning
confidence: 99%